Ô nhiễm kim loại nặng trong đất và trầm tích tại một số bãi thu gom và tái chế chất thải điện tử. - Thảo và cộng sự, Tạ Thị (Vietnam Journal of Chemistry, 2014)
Heavy metal contamination in soil and sediment from electronic rubbishes and plastic treatment places can be harmful to the biota and human beings. In this report, 43 samples of soil and sediment from e-waste collecting and recycling places (Phan Boi small village, Di Su commune, My Hao district, Hung Yen province and Trieu Khuc village, Thanh Tri district, Ha Noi Town) and 9 urban and non-urban soil profiles were analyzed for total contents of Cr, Mn, Fe, Co, Ni, Cu, Zn, As, Cd, Pb, Hg using ICP-MS and CV-AAS. The soils and sediment were polluted with Co, Ni, Cu, Zn and heavily polluted with As, Hg Cd and Pb. The contents of Zn, As, Pb increased with the increase of distance from the e-waste collecting fields. The mean total contents of almost heavy metals in sediment are many times higher than the mean value of surface soil and the natural value of soil. The results also showed the marked decrease of heavy metal content by vertical depth. For the environmentally safe purpose as well as sour apportionment of heavy metals of soil and sediment, the extraction procedure and multivariate analysis will be investigated in further work.